Intervention with conviction-confidence model for non-obese high school students to prevent unhealthy dieting: a cluster randomized control trial - Takasawa, Naomi; Hamaguchi, Sugihiro; Kanke, Satoshi (FUKUSHIMA JOURNAL OF MEDICAL SCIENCE, 2025)
Background:Unhealthy dieting behaviors to lose weight in adolescents can cause future health issues such as mineral, hormonal, or bone complications, highlighting the importance of preventive interventions.Methods:Six classes consisting of 236 first-year high school students were randomly allocated to an intervention group, which participated in interactive healthy eating and dieting programs, or to a control group, which attended a smoking prevention workshop. Data from non-obese students were analyzed, comparing the dieting behaviors of both groups at a two-month follow-up. Self-reported questionnaires assessed conviction and confidence levels about healthy eating and dieting after the intervention.Results:The two groups did not differ in the proportion of students engaging in dieting behavior after the intervention (intervention:14.9% vs. control:22.7%, p=0.18). The intervention increased the conviction level regarding healthy eating (90.4% vs. 74.7%, p<0.01) but not the confidence level (50.0% vs. 36.0%, p=0.06);it did not significantly impact conviction and confidence levels regarding healthy dieting (62.8% vs. 61.4%, p=0.84;45.7% vs. 37.5%, p=0.26).Conclusions:The classroom-based intervention failed to prevent unhealthy dieting behavior among non-obese students. Interventions boosting conviction and confidence, thereby preventing unhealthy dieting among all students, regardless of risk factors such as eating disorder tendencies, require further research.